Labour Market Imbalances in Canada, 1966-1983 - Betcherman, Gordon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper considers two questions. First, what imbalance trends have characterized the Canadian labour market since 1966? And, second, what factors explain these trends.